Effect of Pilates Exercises on Motor Performance and Low Back Pain in Elderly Women With Abdominal Obesity - Ali Seghatoleslami; Ali Hemmati Afif; Khadijeh Irandoust; Morteza Taheri (University of Social Welfare & Rehabilitation Sciences, 2018)
Objectives This research aimed to investigate the impact of Pilates exercise on motor performance indexes and low back pain of inactive middle-aged women.  Methods & Materials This was a quasi-experimental study with pretest and posttest design performed on 43 inactive females with mean (SD) age of 44.4 (5.1) year with low activity, body fat percentage above 35%, and Waist Hip Ratio (WHR) of over 0.95. They were assigned into test (n=22) and control (n=21) group. The Pilates or test group did their exercise for 4 months, three times a week while the control group did their daily routines. All body composition variables were measured by body composition analyzer and functional tests were measured by speed and balance tests. Independent and dependent t test were used to analyze the data.  Results The results suggested that dynamic balance and speed improved significantly and those effective factors on motor control such as obesity variables, including Body Mass Index (BMI), WHR, body fat percentage, visceral fat were also improved (P≤0.05). Conclusion It seems that Pilates exercise may improve motor performance indexes and also a better quality of life due to a mitigating low back pain. Therefore, practicing such an exercise program can be effective in older persons.